2007
DOI: 10.2174/156800907783220462
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Regulators of Cancer Angiogenesis

Abstract: Current cancer chemotherapeutic drugs have limited efficacy due to the fact that tumour cells are a rapidly changing target characterised by genomic instability. Unlike tumour cells, activated endothelial cells (ECs) required for angiogenesis, a process indisputably crucial to tumour growth and metastasis, were originally considered to be ideal therapeutic targets free of drug resistance. Additionally, unlike preclinical studies in mice using inhibitors targeting the powerful EC mitogen--vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 177 publications
(259 reference statements)
1
36
0
1
Order By: Relevance
“…The activation of angiogenesis is a critical step in cancer development (8), involving several kinds of stimulation, such as hypoxia, cytokines, and growth factors (7,(9)(10). Hypoxiainducible factor-1α (HIF-1α) is a pivotal transcription factor that regulates angiogenesis by inducing the expression of vascular endothelial growth factor (VEGF), interleukin-8 (IL-8), and basic fibroblast growth factor (bFGF; ref.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of angiogenesis is a critical step in cancer development (8), involving several kinds of stimulation, such as hypoxia, cytokines, and growth factors (7,(9)(10). Hypoxiainducible factor-1α (HIF-1α) is a pivotal transcription factor that regulates angiogenesis by inducing the expression of vascular endothelial growth factor (VEGF), interleukin-8 (IL-8), and basic fibroblast growth factor (bFGF; ref.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most crucial components of the TME in promoting tumor growth, invasion, and metastasis. Studies indicated that CAFs produce and secrete many growth factors and cytokines such as TGF-ÎČ, hepatocyte growth factor (HGF), and fibroblast secreted protein-1 (FSP1) to support primary tumor growth [40,41]. CAFs can also promote angiogenesis by secreting stromal derived factor1 (SDF-1) to recruit endothelial cell precursors (EPCs) [41].…”
Section: Cellular Components In the Tme That Suppress Tumor Progressionmentioning
confidence: 99%
“…Studies indicated that CAFs produce and secrete many growth factors and cytokines such as TGF-ÎČ, hepatocyte growth factor (HGF), and fibroblast secreted protein-1 (FSP1) to support primary tumor growth [40,41]. CAFs can also promote angiogenesis by secreting stromal derived factor1 (SDF-1) to recruit endothelial cell precursors (EPCs) [41]. Interestingly, SDF-1α (also known as CXCL12) binds to CXCR4 in tumors cells to directly stimulate cancer cell proliferation [42].…”
Section: Cellular Components In the Tme That Suppress Tumor Progressionmentioning
confidence: 99%
“…So far more than a dozen proangiogenic molecules have been reported to play an important role in tumor angiogenesis [Bouck et al, 1996;Cockerill et al, 1995;Folkman, 1995Folkman, , 1997. In addition to its predominant role in the vascular compartment, the combination of stromal cells and the microenvironment around the tumor niche may lead to the development of a variety of cancers [Barcellos-Hoff and Ravani, 2000;Bhowmick et al, 2004;Coussens and Werb, 2002;Cunha et al, 2003;Goh et al, 2007;Olumi et al, 1999]. Although the list of molecular and cellular players involved in regulation of tumor blood vessel formation is growing, we will focus and highlight only the major players.…”
Section: Molecular and Cellular Players Of Tumor Angiogenesismentioning
confidence: 99%